Flipped classroom and digital technologies: Didatic possibility for Science teaching in an active methodology proposal - Silva, Iasmim Ferreira da (2022)
In this text, we presented some analyzes and reflections on a Didactic Sequence developed with 25 high school students from a federal public institution, located in the Brazilian Midwest, during the period of Remote Education are presented. We opted for an adaptation of the Flipped Classroom (SAI, in Portuguese), alternating asynchronous moments in the Virtual Learning Environment with synchronous moments, through Google Meet. We work on dialogic strategies, aiming at student protagonism, based on forums and questions about the relationship between the veracity of information and scientific criteria. The students were instructed to seek reasons for the news broadcast referring to the new Coronavirus, Sars-Cov-2. From the research carried out, it was possible to infer that the structured didactic sequence allowed the creation of spaces for dialogicity, triggering actions of clash of ideas, refuting and arguing unreliable information and also enabling academic production (for example, some presentations to other students), on the part of students.